2011
DOI: 10.1161/atvbaha.111.238261
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor-2 Modulates Protease-Activated Receptor-1–Driven Neointimal Hyperplasia

Abstract: Objective Emerging evidence suggests that protease-activated receptors-1 and 2 (PAR1 and PAR2) can signal together in response to proteases found in the rapidly changing microenvironment of damaged blood vessels. However, it is unknown whether PAR1 and PAR2 promote or mitigate the hyperplastic response to arterial injury. Using cell-penetrating PAR1 pepducins and mice-deficient in PAR1 or PAR2, we set out to determine the respective contributions of the receptors to hyperplasia and phenotypic modulation of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 44 publications
(59 reference statements)
4
72
0
2
Order By: Relevance
“…The focus of our studies was to characterize the changes in gene expression Various studies have shown that PAR1 can trans-activate PAR2 [115][116][117][118]149 .We examined the possible role of receptor dimerization between PAR1 and PAR2 by over-expressing SEAP-PAR1 and PAR2-Flag in HEK293T or A549 cells but did not find any evidence that this leads to a major change in either the activation or cleavage of these receptors (data not shown). Similarly, some Gla domaincontaining proteases such as APC and FXa need the co-receptor, EPCR to facilitate PAR activation 98,122 .…”
Section: Discussionmentioning
confidence: 99%
“…The focus of our studies was to characterize the changes in gene expression Various studies have shown that PAR1 can trans-activate PAR2 [115][116][117][118]149 .We examined the possible role of receptor dimerization between PAR1 and PAR2 by over-expressing SEAP-PAR1 and PAR2-Flag in HEK293T or A549 cells but did not find any evidence that this leads to a major change in either the activation or cleavage of these receptors (data not shown). Similarly, some Gla domaincontaining proteases such as APC and FXa need the co-receptor, EPCR to facilitate PAR activation 98,122 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kaneider et al (16) showed that PAR2 associates with PAR1 in endothelial cells during late stages of sepsis and switches thrombin signaling from barrier-disruptive to barrier-protective. In other work, PAR2 expression was shown to be necessary for PAR1-induced hyperplasia in vascular smooth muscle cells (17). The ability of PAR1 to transactivate PAR2 would necessitate that the two receptors be in close proximity, likely in the form of a heterodimer.…”
mentioning
confidence: 95%
“…The ability of PAR1 to transactivate PAR2 would necessitate that the two receptors be in close proximity, likely in the form of a heterodimer. Two previous studies have suggested that PAR1 and PAR2 associate (16,17). However, the mechanisms that govern PAR1-PAR2 heterodimer formation, trafficking, and signaling have not been investigated.…”
mentioning
confidence: 98%
“…При лечении им мышей на протяжении 21 дня в дозе 2,5 мг/кг наблюдалась сильно выраженная гиперплазия неоинтимы в повреждённой сонной артерии [30]. Область неоинтимы при обработке пепдуцином P1pal-13 увеличивалась в 13 раз в сравнении с контролем, что приводило к полному стенозу сонной артерии.…”
Section: влияние на ангиогенез развитие злокачественных опухолей и мunclassified
“…Тот факт, что у мышей, нокаутных по генам, кодирующим PAR1-рецептор, проангиогенное действие пепдуцина не выявлялось, указывает на определяющую роль гомологичного ему рецептора в молекулярных механизмах действия пепдуцина. Гиперпластический эффект пепдуцина P1pal-13 также отсутствовал у мышей, нокаутных по гену PAR2-рецептора, что свидетельствует о необходимости образования гетеродимерных PAR1-PAR2 комплексов для функциональной активности PAR1-рецептора [30]. Активация PAR1-рецептора металло-протеиназой-1, которая выполняет функции PAR1-агониста, в фолликулярных клетках яичников приводила к усилению секреции соседними эндотелиальными клетками ангиогенных хемокинов, в первую очередь, интерлейкина-8 и хемокина CXCL1/GRO-a, и к повышению экспрессии чувствительных к ним хемокиновых рецепторов CXCR1 и CXCR2 [31].…”
Section: влияние на ангиогенез развитие злокачественных опухолей и мunclassified